Mountains and the German mind translations from Gessner to Messner, 1541-2009 - Ireton, Sean Moore 1965-; Schaumann, Caroline (Studies in German literature, linguistics, and culture, 2020)
Mountains have occupied a central place in German, Swiss, and Austrian intellectual culture for centuries. This volume offers the first scholarly English translations of thirteen key texts from the Germanophone tradition of engagement with mountains. The selected texts span over 450 years, ranging from the early modern period to the postmodern era, and encompass several discursive modes of the mountain experience including geographical descriptions, philosophical meditations, aesthetic deliberations, and autobiographical climbing narratives. Well-known figures covered in this translational sourcebook include Conrad Gessner, Johann Jakob Scheuchzer, G.W.F. Hegel, Alexander von Humboldt, Georg Simmel, Leni Riefenstahl, and Reinhold Messner. Each text is accompanied by a critical introduction that places the translated text within a broader cultural context. The dual translational-interpretational approach offered in this volume is intended to stimulate new international and interdisciplinary dialogue on the cultural history of mountains and mountaineering